Employment and wage effects of extending collective bargaining agreements - Ernesto Villanueva; Effrosyni Adamopoulou (IZA World of Labor, 2022)
In many countries, the wage floors and working conditions set in collective contracts negotiated by a subset of employers and unions are subsequently extended to all employees in an industry. Those extensions ensure common working conditions within the industry, mitigate wage inequality, and reduce gender wage gaps. However, little is known about the so-called bite of collective contracts and whether they limit wage adjustments for all workers. Evidence suggests that collective contract benefits come at the cost of reduced employment levels, though typically only for workers earning close to the wage floors.
Keywords: J23; J31; E24; 330; bite of collective contracts; wage inequality; employment losses